“They’re trying to influence me to gain the more acceptable viewpoint”: The algorithmic imaginaries of politically activated social media users - Maragh-Lloyd, Raven; Stoldt, Ryan; Ssozi, Javie; Biddle, Kathryn; Ekdale, Brian; Havens, Tim (New media & society, 2025)
Links between extremism online and personalization algorithms are, by now, widely accepted. However, discussions surrounding sociopolitical radicalization and its relationship to filter bubbles often fail to account for user agency. Based on interview ( N = 29) and survey ( N = 1100) data, our study asks how politically engaged social media users make sense of algorithmic personalization related to political topics of interest. Our results indicate that most respondents conceptualize personalization as a functional process of social media platforms seeking to deliver relevant information, while a small but vocal number of users claim algorithms are designed not to personalize content but rather to enact an ideological agenda. Our findings, which include real-time user responses to algorithms, suggest that algorithms do not simply radicalize unsuspecting users but, rather, are negotiated to reveal a more complex digital landscape.